Combined study of ADAMTS13 and complement genes in the diagnosis of thrombotic microangiopathies using next-generation sequencing - Fidalgo, T (2017)
BACKGROUND: The 2 main forms of thrombotic microangiopathy (TMA) are thrombotic thrombocytopenic purpura (TTP) and atypical hemolytic uremic syndrome (aHUS). Deficiency of ADAMTS13 and dysregulation of the complement pathway result in TTP and aHUS, respectively; however, overlap of their clinical characteristics makes differential diagnosis challenging. OBJECTIVES AND METHODS: We aimed to develop a TMA diagnosis workflow based on ADAMTS13 activity and screening of ADAMTS13 and complement genes using a custom next-generation sequencing (NGS) gene panel. PATIENTS: For this, from a cohort of 154 Portuguese patients with acute TMA, the genotype-phenotype correlations were analyzed in 7 hereditary TTP (ADAMTS13 activity <10%, no inhibitor), 36 acquired TTP (ADAMTS13 activity <10%, presence of an inhibitor), and in 34 presumable aHUS. RESULTS: In total, 37 different rare variants, 8 of which novel (in ADAMTS13,CFH, and CD46), were identified across 7 genes. Thirteen TTP patients were homozygous (n=6), compound heterozygous (n=2), and heterozygous (n=5) for 11 ADAMTS13 variants (6 pathogenic mutations). Among the 34 aHUS patients, 17 were heterozygous for 23 variants in the different complement genes with distinct consequences, ranging from single pathogenic mutations associated with complete disease penetrance to benign variants that cause aHUS only when combined with other variants and/or CFH and CD46 risk haplotypes or CFHR1-3 deletion. CONCLUSIONS: Our study provides evidence of the usefulness of the NGS panel as an excellent technology that enables more rapid diagnosis of TMA, and is a valuable asset in clinical practice to discriminate between TTP and aHUS.